Sustainable practices and financial performance in fashion firms. Issue 1 (25th May 2021) - Medcalfe, Simon; Miralles Miro, Eva
Abstract : Purpose: The purpose of this paper is to determine the relationship between sustainable practices and financial performance in fashion firms. Design/methodology/approach: A statistical analysis (fixed effects and ordinary least squares) of publicly available financial data combined with sustainable practices taken from the Baptist World Aid Australia Ethical Fashion Reports to determine if companies with better sustainable practices have significantly better financial performance. Findings: The research shows that there is a strong positive correlation between sustainable practices and financial performance in fashion firms. There is stronger evidence that better sustainable practices lead to better financial performance and vice versa. Research limitations/implications: The sample size is limited to publicly available financial data and may not be generalized to all fashion firms. A quarter of firms were unresponsive to Baptist World Aid Australia's requests for information on sustainable practices creating potential selection bias. Social implications: Consumers, employees, government and non-governmental organizations are advocates for greater corporate responsibility in fashion firms. Given the positive relationship between sustainable practices and return on equity, shareholders can be added to this list. Originality/value: This research is the first to analyze objective financial performance with a range of sustainable indicators to determine if certain practices are more valuable than others.